DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

Multispecies toxicity evaluation of extractable chemicals from commercial biodegradable plastic products - Soyeon An; Hwicheol Shin; In-Cheol Yeo; Chang-Bum Jeong; Dong-Ku Kang (Journal of Hazardous Materials, 2026)

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Evaluation of total nitrogen stocks and burial rates in salt marshes and bare flats of Marine National Parks in South Korea - Inha Kwon; Taewoo Kim; Seo Joon Yoon; Shin Yeong Park; In Ok Lee; Dong-U Kim; Hosang Kim; Cheongjae Lee; Young Eun Kim; Changkeun Lee; Bong-Oh Kwon; Jung Kwan Ahn; et al. (Regional Studies in Marine Science, 2025)

First report of Erysiphe lonicerae causing powdery mildew on goldflame honeysuckle (Lonicera × heckrottii) in Korea - Lamiya Abasova; In-Young Choi; Hye-Ryeong Jang; Ji-Hyun Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2025)

Occurrence and composition of PFAS in disposable straws from the Korean Market: quantitative and suspect screening analyses - Hyeri Jeon; Ye-Ju Shin; Ye-In Kim; Dong-Su Kim; Hyewon Shin; Younglim Kho (Environmental Science and Pollution Research, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Holomorph morphology and molecular phylogeny confirm Erysiphe necator var. necator causing powdery mildew on Vitis flexuosa in Korea - Ji-Hyun Park; Lamiya Abasova; In-Young Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

First report of Erysiphe aquilegiae causing powdery mildew on Chinese buttercup (Ranunculus cantoniensis) in Korea - In-Young Choi; Lamiya Abasova; Byoung-Ki Choi; Hyeon-Dong Shin; Ji-Hyun Park (Journal of Plant Pathology, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Microcystis abundance is predictable through ambient bacterial communities: A data-oriented approach - Mingyeong Kang; Dong-Kyun Kim; Ve Van Le; So-Ra Ko; Jay Jung Lee; In-Chan Choi; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Journal of Environmental Management, 2024)

Revisiting Pseudocercospora puerariicola associated with leaf spot on Pueraria montana var. lobata with morphological and molecular-phylogenetic data in Korea - In-Young Choi; Lamiya Abasova; Ji-Hyun Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2024)

Correction to: Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)

Comparison of skin dose in IMRT and VMAT with TrueBeam and Halcyon linear accelerator for whole breast irradiation - Jae Hyun Seok; So Hyun Ahn; Woo Sang Ahn; Dong Hyeok Choi; Seong Soo Shin; Wonsik Choi; In-hye Jung; Rena Lee; Jin Sung Kim (Physical and Engineering Sciences in Medicine, 2024)
With the increasing use of flattening filter free (FFF) beams, it is important to evaluate the impact on the skin dose and target coverage of breast cancer treatments. This study aimed to compare skin doses of treatments using FFF and flattening filter (FF) beams for breast cancer. The study established treatment plans for left breast of an anthropomorphic phantom using Halcyon’s 6-MV FFF beam and TrueBeam’s 6-MV FF beam. Volumetric modulated arc therapy (VMAT) with varying numbers of arcs and intensity modulated radiation therapy (IMRT) were employed, and skin doses were measured at five points using Gafchromic EBT3 film. Each measurement was repeated three times, and averaged to reduce uncertainty. All plans were compared in terms of plan quality to ensure homogeneous target coverage. The study found that when using VMAT with two, four, and six arcs, in-field doses were 19%, 15%, and 6% higher, respectively, when using Halcyon compared to TrueBeam. Additionally, when using two arcs for VMAT, in-field doses were 10% and 15% higher compared to four and six arcs when using Halcyon. Finally, in-field dose from Halcyon using IMRT was about 1% higher than when using TrueBeam. Our research confirmed that when treating breast cancer with FFF beams, skin dose is higher than with traditional FF beams. Moreover, number of arcs used in VMAT treatment with FFF beams affects skin dose to the patient. To maintain a skin dose similar to that of FF beams when using Halcyon, it may be worth considering increasing the number of arcs.

First report of powdery mildew caused by Erysiphe mori on Morus cathayana in Korea - In-Young Choi; Lamiya Abasova; Hyeon-Dong Shin; Ji-Hyun Park (Journal of Plant Pathology, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Correction to: Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Holomorph morphology and molecular phylogeny of Podosphaera macularis causing powdery mildew on Humulus scandens in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Chong-Kyu Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

First report of powdery mildew caused by Erysiphe deutziae on Deutzia parviflora in Korea - Kui-Jae Lee; In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

Cold-induced adaptive thermogenesis is impaired by exposure of Asian sand dust in mice - Bernadette B. Bagon; Junhyeong Lee; Merc Emil Matienzo; Se-Jin Lee; So-Won Pak; Keon Kim; Jeongmin Lee; Chang-Min Lee; In-Sik Shin; Changjong Moon; Min-Jung Park; Dong-il Kim (Journal of Thermal Biology, 2023)

First report of powdery mildew caused by Erysiphe pulchra on Cornus kousa in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Chong-Kyu Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

First report of powdery mildew caused by Phyllactinia japonica on Fraxinus sieboldiana in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Jung-Hee Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

First report of powdery mildew caused by Erysiphe heraclei on Anthriscus caucalis in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2023)

First report of powdery mildew caused by Podosphaera elsholtziae on Ajuga decumbens in Korea - In-Young Choi; Joon-Ho Choi; Lamiya Abasova; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

Geochemical signatures of organic matter associated with gas generation in the Pohang Basin, South Korea - Dong-Hun Lee; Seung-Hee Kim; Jiyoung Choi; Nyeon-Keon Kang; In Gul Hwang; Kyung-Hoon Shin (Geosciences Journal, 2022)

Oculomics for sarcopenia prediction: a machine learning approach toward predictive, preventive, and personalized medicine - Bo Ram Kim; Tae Keun Yoo; Hong Kyu Kim; Ik Hee Ryu; Jin Kuk Kim; In Sik Lee; Jung Soo Kim; Dong-Hyeok Shin; Young-Sang Kim; Bom Taeck Kim (EPMA Journal, 2022)

First report of powdery mildew caused by Erysiphe lonicerae on Lonicera periclymenum in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of powdery mildew caused by Erysiphe russellii on Oxalis dillenii in Korea - In-Young Choi; Lamiya Abasova; Joon-Ho Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of powdery mildew caused by Podosphaera xanthii on Matricaria chamomilla in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of powdery mildew caused by Erysiphe polygoni on Rumex japonicus in Korea - In-Young Choi; Hyun-Myung Oh; Sun-Hee Hong; Young-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of powdery mildew caused by Podosphaera astericola on Kalimeris incisa in Korea - In-Young Choi; Chong-Kyu Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of rust caused by Coleosporium zanthoxyli on Zanthoxylum piperitum in Korea - Young-Joon Choi; Jae-Sung Lee; In-Young Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

First report of powdery mildew caused by Podosphaera sibirica on Veronicastrum sibiricum in Korea - In-Young Choi; Ji-Hyun Park; Bok-Nam Jung; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

First report of powdery mildew caused by Podosphaera erigerontis-canadensis on Conyza sumatrensis in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

First report of powdery mildew caused by Erysiphe glycines on Hylodesmum podocarpum in Korea - In-Young Choi; Young-Joon Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2020)

First report of powdery mildew caused by Podosphaera xanthii on Cucurbita maxima in Korea - In-Young Choi; Young-Joon Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2020)

Anti-skin ageing effects of phenolic compounds from Carpinus tschonoskii - Jun Yin; Hye Shin Ahn; Seong Yi Ha; In Hyeok Hwang; Kee Dong Yoon; Young Won Chin; Min Won Lee (Natural Product Research, 2019)

Genetic characterization of bovine coronavirus in Vietnam - Jihye Shin; Dongseob Tark; Van Phan Le; SeEun Choe; Ra Mi Cha; Gyu-Nam Park; In-Soo Cho; Bui Thi To Nga; Nguyen Thi Lan; Dong-Jun An (Virus Genes, 2019)

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Perofascia is not monotypic: the description of the second taxon affecting the South American crop maca (Lepidium meyenii) - Young-Joon Choi; Marco Thines; In-Young Choi; Hyeon-Dong Shin (Mycological Progress, 2017)

Effective selection of soybean cultivars to wildfire disease pathogen Pseudomonas amygdali pv. tabaci - In Jeong Kang; Seung-Han Kim; Yong Weon Seo; Min Jeong Seo; Hyeong Kwon Shim; Dong Bum Shin; Sunggi Heu (Journal of Crop Science and Biotechnology, 2015)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

SMOC1-induced osteoblast differentiation involves enhanced proliferation of human bone marrow mesenchymal stem cells - Young-Ae Choi; Dong-Sung Kim; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2014)

The anti-inflammatory effects of Alisma herb extract on allergic asthma mouse model - Min-Hee Shin; Yu Jin Park; Ki-Suk Kim; Dong Hyuk Cho; In Joon Uh; Kang-Hoon Kim; In Jin Ha; Won-Seok Chung; Hee-Jae Jung; Sung-Ki Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2014)

Silver nanoparticles induce apoptotic cell death in cultured cerebral cortical neurons - Sung-Hwan Kim; Je-Won Ko; Suk-Kyu Koh; In-Chul Lee; Jung-Mo Son; Changjong Moon; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Molecular evidence for hybrid origin of Aster chusanensis, an endemic species of Ulleungdo, Korea - Hyunchur Shin; Sang-Hun Oh; Yongseok Lim; Chang-Woo Hyun; Seong-Hyun Cho; Yong-In Kim; Young-Dong Kim (Journal of Plant Biology, 2014)

Osteogenic activity of chitosan-based hybrid scaffold prepared by polyelectrolyte complex formation with alginate - Seung Hwan Lee; Ho Yun Chung; Hong-In Shin; Dong-Joon Park; Jin Hyun Choi (Tissue Engineering and Regenerative Medicine, 2014)

Erratum to: Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2013)

Pycnogenol® prevents hexavalent chromium-induced spermatotoxicity in rats - Sung-Hwan Kim; In-Chul Lee; Hyung-Seon Baek; Changjong Moon; Seong-Soo Kang; Chun-Sik Bae; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2012)

Regulation of arterial blood pressure by Akt1-dependent vascular relaxation - Jung Min Ha; Young Whan Kim; Dong Hyung Lee; Sung Ji Yun; Eun Kyoung Kim; In Hye Jin; Ji Hyun Kim; Chi Dae Kim; Hwa Kyoung Shin; Sun Sik Bae (Journal of Molecular Medicine, 2011)

Association of tumor necrosis factor-α (TNF-α) promoter polymorphisms with overweight/obesity in a Korean population - Gyeong-Im Yu; Eunyoung Ha; Sung-Hee Park; Jae-Hyung Park; Hyun-Sook Jang; Jae-Hoon Bae; In-Sung Chung; Dong-Hoon Shin; Dae-Kyu Song (Inflammation Research, 2011)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

Effect of light on endogenous levels of gibberellin and abscisic acid in seed germination of photoblastic weedy rice (Oryza sativa L.) - Sang-Yeol Kim; Sun-Joo Hwang; In-Jung Lee; Dong-Hyun Shin; Sung-Tae Park; Un-Sang Yeo; Hang-Won Kang (Journal of Crop Science and Biotechnology, 2009)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Fatty acid composition in each structural part of soybean seed and sprout - Krishna Hari Dhakal; Yeon-Shin Jeong; Jeong-Dong Lee; In-Youl Baek; Tae-Joung Ha; Young-Hyun Hwang (Journal of Crop Science and Biotechnology, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

Molecular authentication of ginseng cultivars by comparison of internal transcribed spacer and 5.8S rDNA sequences - Ok Tae Kim; Kyong Hwan Bang; Dong Su In; Jei Wan Lee; Young Chang Kim; Yoo Soo Shin; Dong Yun Hyun; Sung Sik Lee; Seon Woo Cha; Nak Sul Seong (Plant Biotechnology Reports, 2007)

Antiangiogenic and Apoptotic Properties of a Novel Amphiphilic Folate-Heparin-Lithocholate Derivative Having Cellular Internality for Cancer Therapy - Mi Kyung Yu; Dong Yun Lee; Yoo Shin Kim; Kyeongsoon Park; Soo Ah Park; Dai Hyun Son; Gee Young Lee; Jong Hee Nam; Sang Yoon Kim; In San Kim; Rang Woon Park; Youngro Byun (Pharmaceutical Research, 2007)

Assessment of random amplified polymorphic DNA (RAPD) for determining the origin ofYoungia koidzumiana Kitamura (compositae) - Kyoung-Hwan Tae; Dong Su In; Kee-Sun Shin (Journal of Plant Biology, 2001)

A shoot regeneration protocol effective on diverse genotypes of sunflower (Helianthus annuus L.) - Dong-Ho Shin; Jin Sook Kim; In Jeong Kim; Jaemo Yang; Soo Kyung Oh; Gab Chae Chung; Kyung-Hwan Han (In Vitro Cellular & Developmental Biology - Plant, 2000)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Pharmacokinetic-pharmacodynamic modeling of risperidone effects on electroencephalography in healthy volunteers - Dong Young Lee; Kang Uk Lee; Jun Soo Kwon; In Jin Jang; Maeng Je Cho; Sang Goo Shin; J. I. Woo (Psychopharmacology, 1999)

Expression and secretion of Clostridium thermocellum endoglucanase A gene (celA) in different Saccharomyces cerevisiae strains - Dae-Kyun Chung; Dong-Ha Shin; Byung-Woo Kim; Jae-Kook Nam; In-Seob Han; Soo-Wan Nam (Biotechnology Letters, 1997)